2014
DOI: 10.1097/hjh.0000000000000100
|View full text |Cite
|
Sign up to set email alerts
|

Differential relationships of systolic and diastolic blood pressure with components of left ventricular diastolic dysfunction

Abstract: Both SBP and DBP are important determinants of separate components of left ventricular diastolic dysfunction and these effects are noted even within normotensive BP ranges. DBP may be as important as SBP in the transition to diastolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 43 publications
0
16
2
Order By: Relevance
“…Logistic regression analysis was performed to determine the relative independent effects of indices of adiposity versus SBP or DBP on measures of diastolic function considered as categorical traits. As we have recently demonstrated that SBP is more closely related to E/e 0 and DBP to E/A [17], SBP was employed in models with E/e 0 and DBP in models with E/A. The following additional parameters were included in the regression models: age, sex, regular alcohol or tobacco use, the presence or absence of diabetes mellitus or inappropriate blood glucose control (considered as a single covariate), the use of antihypertensive agents, and pulse rate.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Logistic regression analysis was performed to determine the relative independent effects of indices of adiposity versus SBP or DBP on measures of diastolic function considered as categorical traits. As we have recently demonstrated that SBP is more closely related to E/e 0 and DBP to E/A [17], SBP was employed in models with E/e 0 and DBP in models with E/A. The following additional parameters were included in the regression models: age, sex, regular alcohol or tobacco use, the presence or absence of diabetes mellitus or inappropriate blood glucose control (considered as a single covariate), the use of antihypertensive agents, and pulse rate.…”
Section: Discussionmentioning
confidence: 89%
“…Clinical, demographic, anthropometric, and blood pressure measurements A standardized questionnaire was administered to obtain demographic and clinical data [17][18][19]. Height, weight, waist circumference, and hip circumference were measured using the standard approaches and participants were identified as being overweight if their BMI was at least 25 kg/m 2 , obese if their BMI was at least 30 kg/m 2 , and morbidly obese if their BMI was at least 35 kg/m 2 .…”
Section: Study Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Left ventricular hypertrophy (LVH) was identified as LVMI above 51 g/m 2.7 [28]. Left ventricular diastolic function was assessed from a pulsed wave Doppler examination of the mitral inflow at rest [29]. Transmitral flow velocity in early (E) and late (atrial) diastole was assessed and data expressed as E/A.…”
Section: End-organ Measuresmentioning
confidence: 99%